A Self-Sovereign Identity–Blockchain-Based Model Proposal for Deep Digital Transformation in the Healthcare Sector - Luisanna Cocco; Roberto Tonelli (Future Internet)
The acceleration of the digital transformation process imposed by the pandemic in all the countries of the European Union, and in all sectors, has given way to a revolution that up until a couple of years ago would have been impossible even to imagine. Digital innovation has become a factor of competitiveness in all sectors. In this new scenario that has come to be, the Blockchain technology, the Self-Sovereign Identity paradigm, Internet of Things, and, in general, the new technologies that will emerge, will constitute enhancers of competitiveness and will have to aim for interoperability. In this context, this article develops and presents a model proposal in the healthcare field that aims to highlight how the combination of the Blockchain technology and the Self-Sovereign Identity paradigm restores full control over a person’s identity and information, while ensuring the integrity of all medical reports, enabling secure communications between personal medical devices and patient/doctor applications on devices exploiting peer Decentralized Identifiers and ensuring data privacy, exploiting Zero Knowledge Proofs. The proposal relies on the Veramo platform, treating all medical reports as verifiable credentials and storing them in digital wallets owned by the patient. The article concludes by presenting a prototype designed and implemented for managing medication prescriptions, their issuance, and their exchange.